1999
DOI: 10.1210/jcem.84.9.5991
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1108, DRB1103/DRB310101, and DRB310202 Are Susceptibility Genes for Graves’ Disease in North American Caucasians, Whereas DRB1107 Is Protective1

Abstract: Graves' disease is known to be HLA-D associated; however, the primary loci involved remain unclear. We examined HLA genotypes of DRB1 and DQB1 plus DRB3 subtypes using PCR-based sequence-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 25 publications
2
41
1
1
Order By: Relevance
“…Indeed, analysis of electronic sequence databases indicated that DRb-Gln74 is always present on DR7, an allele that was found to be protective for GD in our data set (DR7 was found in 10.1% of our GD patients and in 17.0% of the controls, w 2 ¼ 4.1, P ¼ 0.04), as well as in other Caucasian datasets. 19 This suggests that position 74 of the DRb1 chain is critical for GD development, with DRb-Arg74 conferring susceptibility and DRb-Gln74 conferring protection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analysis of electronic sequence databases indicated that DRb-Gln74 is always present on DR7, an allele that was found to be protective for GD in our data set (DR7 was found in 10.1% of our GD patients and in 17.0% of the controls, w 2 ¼ 4.1, P ¼ 0.04), as well as in other Caucasian datasets. 19 This suggests that position 74 of the DRb1 chain is critical for GD development, with DRb-Arg74 conferring susceptibility and DRb-Gln74 conferring protection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the DRB3 gene-encoded molecules have not been as well studied as those encoded by DRB1 genes, these MHCII molecules have been linked to several autoimmune diseases; for example, DR52a has been associated with Crohn's sarcoidosis (8), Graves' disease (9,10), and Löfgren's syndrome (11); DR52b has been associated with Graves' disease (12), multiple sclerosis (13), and essential hypertension caused by Chlamydia pneumoniae infection (14); and DR52c has been related to Crohn's disease (15) and cedar pollen allergies (16). Recently, we identified DR52c as the MHC-restriction element for a human nickel-reactive T cell isolated from a patient with contact sensitivity to nickel in jewelry (4).…”
mentioning
confidence: 99%
“…In the previous studies, the associations between age at onset and different HLA genotypes in Caucasians (18), and Japanese (19), and ICAM-1 gene alleles in Caucasians (20) and CD40 genotypes in Japanese (21), have been reported. Therefore, we evaluated the differences between the frequencies of the CD40 and TG genotypes in Taiwanese patients with GD onset aged below 40 years and those with a later onset of GD.…”
Section: Discussionmentioning
confidence: 98%